Emergent Synchronous Bursting of Oxytocin Neuronal Network - Rossoni, Enrico; Feng, Jianfeng; Tirozzi, Brunello; Brown, David; Leng, Gareth; Moos, Françoise (PLOS Computational Biology, 2008)
Author SummaryWhen young suckle, they are rewarded intermittently with a let-down of milk that results from reflex secretion of the hormone oxytocin. Oxytocin is a neuropeptide made by specialised neurons in the hypothalamus, and is secreted from nerve endings in the pituitary gland. During suckling, every 5 min or so, each of these neurons discharges a brief, intense burst of action potentials; these are propagated down the axons, and release a pulse of oxytocin into the circulation. Here, we have built a computational model to understand how these bursts arise and how they are synchronized. In our model, bursting is an emergent behaviour of a complex system, involving both positive and negative feedbacks, between many, sparsely connected cells. The oxytocin cells are regulated by independent afferent inputs, but they interact by local release of oxytocin and endocannabinoids. Oxytocin released from the dendrites of these cells has a positive-feedback effect, while endocannabinoids have an inhibitory effect by suppressing the afferent input to the cells. Many neurons make peptides that act as messengers within the brain, and many of these are also released from dendrites, so this model may reflect a common pattern-generating mechanism in the brain.